Study of Grammar Structure in Thesis Abstracts of Nursing Students of Stikes Ngudia Husada Madura - Irianto, Dhaniel Prasetyo; Nurniati, Emi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study discusses the analysis of grammar structure in thesis abstracts of nursing program students at the Ngudia Husada Madura Student of Health Sciences (STIKES). The main objective of this study was to understand the dominant pattern of grammatical errors and provide implications for students’ ability to write thesis abstracts. The research method involved collecting thesis abstracts from students and conducting an in-depth analysis of the grammatical structures used. The results revealed that tense-related errors were the most dominant pattern, indicating difficulty in choosing the appropriate tense to present the research results. In addition, complexity in sentence construction was found, which can hinder the understanding of the core message of the research. Errors in the use of subjects and predicates, which affect the logical flow of abstract writing, were also found. The four keywords that emerged from this study were grammar structure analysis, thesis abstracts, nursing students, and STIKES Ngudia Husada Madura. These findings have important implications for abstract writing in nursing theses. Learning strategies that focus on choosing the correct tense, constructing clear sentences, and understanding the subject and predicate must be implemented. In addition, it is necessary to consider factors such as students' previous level of English fluency and educational experience. The integration of English into the nursing curriculum is crucial for improving nursing students' language skills